1979
DOI: 10.1002/lipi.19790811205
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic Analysis of Myrtus communis Fixed Oil

Abstract: Die hohere berechnete Ulkonzentration in der Vollmiscella ergibt sich aus der vom Rechner durchgefuhrten Massenbilanz durch die hoch angesetzte Beladung des Schrots mit Hexan am Feststoffaustritt des Extrakteurs. Eine Berechnung der tatsachlichen Hexankonzentration im Schrotausgehend von den genau bekannten Massenstromen und den gemessenen Ulkonzentrationenergibt 38 Gew.-"/a, wahrend das Simulationsmodell auf Grund einer im Labor an einem relativ kleinen Rohr gemessenen Hexanabtropfkurve von einer Hexankonzent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The berries are also extracted with solvents (2,3); the extract has a tonic action on the nervous system, is effective against eye inflammation and, intriguingly, is reported to influence hair growth (3). Compounds 2 3 5 6 7 8 9 11 12 13 14 15 16 17 18 19 20 21 23 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 The first study reports a very accurate composition for an Iranian oil, using chromatography and spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…The berries are also extracted with solvents (2,3); the extract has a tonic action on the nervous system, is effective against eye inflammation and, intriguingly, is reported to influence hair growth (3). Compounds 2 3 5 6 7 8 9 11 12 13 14 15 16 17 18 19 20 21 23 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 The first study reports a very accurate composition for an Iranian oil, using chromatography and spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…2007). However, little has been undertaken on the fatty acid composition of myrtle fruit (Asif et al. 1979; Çakir 2004; Aidi wannes et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, few work has been done on the fatty acid contents of the M. communis fruits and seeds. M. communis fruits have a significant oil content about 15.40% and are rich in polyunsaturated linoleic acid [21,22]. Messaoud et al were identified approximately 79.10% of the oil studied that the major constituents were α-pinene and 1,8-cineole in Tunisia [Messaoud].…”
Section: Introductionmentioning
confidence: 99%